A Real Time RT-PCR Assay for Rabies Detection in Sarawak - Amina, Rusli (UNIMAS, 2024)
Rabies is a zoonotic, fatal and progressive neurological infection caused by the rabies virus of the genus Lyssavirus and family Rhabdoviridae. It affects all warm-blooded animals but mainly in dogs and the disease is prevalent throughout the world and endemic in many countries. It is also considered as a serious global threat causing an estimated 60,000 human deaths and is responsible for more than 15 million post-exposure prophylaxis (PEP) in our world population every year. Mode of transmission are mostly through bite wounds, open wounds on the skin or through the mucosal surface of infected saliva. In the ongoing rabies outbreak in Sarawak, that started in July 2017, rabies has been reported to cause 59 deaths from 66 human cases (2017-2023). Precise and accurate laboratory diagnosis of rabies in human and animals is important for early treatment and effective prevention and control measures. Although several assays are available for the diagnosis of rabies virus (RABV) infection in animals and humans, the Direct immunofluoroscent test (DFAT) remains the gold standard test most commonly recommended for diagnosis of rabies by both the World Organization for Animal Health (founded as Office International des Epizooties, OIE) and the World Health Organization (WHO). However, it is extremely observer-dependent and experienced laboratories personnel are needed to carry out this method. In this study, a real time RT-PCR assay was developed for rapid rabies detection in Sarawak. The important PCR parameters including primer and probe concentration and annealing temperature were investigated and optimized. The real time RT-PCR assay was validated using a total number of 152 samples by an in-house conventional PCR assay where and 81 samples were tested positive with sequence confirmation and 72 samples were tested negative. The sensitivity and specificity of the assay were evaluated and shown to have a 100% sensitivity and 97% specificity. The performance of real time RT-PCR assay were retrospectively evaluated on 523 suspected animal rabies samples that were tested by DFAT scoring performed by the State Veterinary Diagnostic Laboratory (SVDL) Sarawak. The performance evaluation revealed that the real time assay was able to detect rabies virus with low viral RNA that were not detected by DFAT suggested a superior performance of this assay compared to DFAT. The real time RT-PCR assay developed in this study will help in rapid diagnosis of rabies virus particularly for early detection that will provide a useful early warning system to public health authorities to better respond and manage the ongoing rabies outbreak in Sarawak.